Program Management System for Pusat Sukan Universiti (PSU) - Suriansah, Mohammad Ridhwan; Sahid, Mohd Zanes (Applied Information Technology And Computer Science, 2025)
Within a year, as a university sports organisation, Pusat Sukan Universiti (PSU) can organize tens or hundreds of activities or events, such as seminars, workshops, exhibitions, sports, and others. This project aims to develop an online platform to streamline and automate the PSU’s program approval process. The system will be designed to replace the current manual paperwork with an efficient, web-based solution accessible via the PSU website. Applicants can submit proposals and track their status online, while reviewers will have dedicated dashboards for evaluation. Key findings suggest that the system will significantly reduce approval times and improve transparency, accuracy, and user accessibility. The study concludes with recommendations for further enhancements to optimise the system’s functionality.